Certification of a police officer as a professional standard of his work - O. V. Chornous (Bulletin of Kharkiv National University of Internal Affairs)
Topical issues of certification of police officers have been considered. The approaches of scientists to the definition of such concepts as "certification" of police officers have been studied. The views of scientists on the institute of certification, its legal regulation and the expediency of conducting have been analyzed. The history of the certification procedure and the grounds for its application have been considered, the main characteristics of the attestation and types have been clarified. The purpose of certification is seen in the most rational use of personnel, increasing the efficiency of their work.